The Notion of Personal Moral Culture and its Impact on Ukrainian Language Formation - Oleksiienko, Nataliia (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
This article considers author definition of the notion “moral culture”. The present study analyzes theoretical interpretation of the spiritual nature of the language and its impact on the personal moral culture formation. The particular importance should be attached to philosophical, religious, ethical and pedagogical study searches of the existing situation of the research. The problem of Ukrainian language spreading among the youth has been explained. The present study analyzes the problem of mother tongue learning in educational institutions as a basis of moral education. It has been found out that in order to overcome spiritual-moral crisis in modern Ukrainian society, education must be exercised exceptionally in the standard literary Ukrainian language, due to the fact that it is fundamental principle of the moral culture. The necessity of creation not just linguistic identity, with certain totality of language skills, but also nationally conscious linguistic identity so far as it is a pledge of a person and nation moral culture increase